DDAH1 promoter ‐396 4N insertion variant is associated with increased risk of type 2 diabetes in a gender‐dependent manner - Fasheng Zhu; Chi Zhou; Zheng Wen; Dao Wen Wang (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Asymmetrical dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthases, making it a contributing factor for diabetes. Endogenous ADMA is hydrolyzed by dimethylarginine dimethylaminohydrolase 1 (DDAH1), and a DDAH1 promoter ‐396 4N deletion/insertion polymorphism (DDAH1: ‐396_‐395insGCGT) regulates its transcriptional activity. This study aimed to explore the association between this polymorphism and type 2 diabetes (T2DM). Methods In a case–control study, all participants were genotyped for this polymorphism within two sets of populations (discovery: 1,227 T2DM patients and 1,339 controls; replication: 1,190 patients and 1,651 controls). The disease association was assessed by a unconditional logistic regression model. Homeostasis model assessment calculations were conducted among different genotypes. Results We identified that DDAH1: ‐396_‐395insGCGT insertion allele was significantly associated with increased risk of T2DM (discovery: adjusted odds ratio [OR] = 1.380, 95% CI = 1.128–1.687, p = .002; replication: OR = 1.231, 95% CI = 1.007–1.504, p = .043). The homeostasis model assessment of insulin resistance was increased in participants carrying Ins/Ins alleles (p = .0452). Interestingly, the insertion allele increased the risk of T2DM in males but not in females (male discovery: OR = 1.528, 95% CI = 1.141–2.047, p = .004; replication: OR = 1.439, 95% CI = 1.083–1.911, p = .012; female discovery: OR = 1.218, 95% CI = 0.913–1.626, p = .18; replication: OR = 1.161, 95% CI = 0.871–1.548, p = .308). Conclusion The DDAH1: ‐396_‐395insGCGT insertion allele is associated with increased risk of T2DM in a gender‐dependent manner, affects males but not females.